Intradialytic Flexybility Exercise Terhadap Fatigue Pada Pasien Penyakit Ginjal Kronis - Inayati, Anik; Jumaiyah, Wati; Latipah, Siti (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Chronic kidney disease (CKD) is a global health problem with increasing prevalence and mortality rates, leading most patients to require hemodialysis therapy. However, this procedure often causes complications, particularly fatigue, a condition of physical and mental exhaustion that does not improve with rest, which negatively impacts patients’ activity, psychosocial functioning, and quality of life. Non-pharmacological interventions such as intradialytic flexibility exercise are considered effective in reducing fatigue levels, improving physical function, and supporting the overall health of patients undergoing hemodialysis. To determine the effectiveness of intradialytic flexibility exercise in reducing fatigue among patients with chronic kidney disease. This experimental study employed a one-group pretest–posttest design. The population consisted of all CKD patients undergoing hemodialysis at Dr. H. Abdul Moeloek Regional General Hospital. A total of 15 patients were recruited using purposive sampling. The intervention consisted of intradialytic flexibility exercise administered in 8 sessions over 4 weeks, with each session lasting 10–15 minutes. The research instrument used was the FACIT-Fatigue scale. Intradialytic flexibility exercise was proven effective in reducing fatigue levels among CKD patients undergoing hemodialysis. This was indicated by an increase in the mean FACIT-Fatigue score from baseline to week 2 by 8.267 points, further increasing to 16.133 points at week 4, with an additional improvement of 7.867 points from week 2 to week 4 (p<0.05). These findings indicate that intradialytic flexibility exercise provides a significant and sustained positive impact on reducing fatigue in patients with chronic kidney disease undergoing hemodialysis. Keywords: Intradialytic Flexibility Exercise, Fatigue, Chronic Kidney Disease  ABSTRAK  Penyakit gagal ginjal kronik (GGK) merupakan masalah kesehatan global dengan prevalensi dan angka mortalitas yang terus meningkat, sehingga sebagian besar pasien memerlukan terapi hemodialisis. Namun, prosedur ini kerap menimbulkan komplikasi, terutama berupa fatigue, yaitu kondisi kelelahan fisik dan mental yang tidak membaik dengan istirahat, serta berdampak pada aktivitas, fungsi psikososial, dan kualitas hidup pasien. Intervensi nonfarmakologis seperti intradialytic flexibility exercise diyakini efektif dalam mengurangi tingkat fatigue, meningkatkan fungsi fisik, serta mendukung kualitas kesehatan pasien yang menjalani hemodialisis. Mengetahui efektifitas pemberian intervensi intradialytic flexybility exercise terhadap penurunan fatique Pasien penyakit ginjal kronik. Studi eksperimen, desain one group pretest posttest. Populasi adalah seluruh pasien GGK yang menjalani hemodialisa di RSUD Dr. H. Abdul Moeloek. Besar sampel 15 pasien dengan teknik purposive sampling. intradialytic flexibility exercise pada pasien penyakit ginjal kronis yang menjalani hemodialisis, dilakukan sebanyak  8 sesi dalam waktu 4 minggu, dimana setiap sesi menjalani waktu 10-15 menit latihan. Instrumen penelitian menggunakan FACIT Fatigue. Intradialytic flexibility exercise terbukti efektif menurunkan tingkat fatigue pada pasien gagal ginjal kronik yang menjalani hemodialisis. Hal ini ditunjukkan dengan peningkatan rerata skor FACIT-fatigue dari pengukuran awal ke minggu ke-2 sebesar 8,267 poin, meningkat menjadi 16,133 poin pada minggu ke-4, serta tambahan peningkatan 7,867 poin dari minggu ke-2 ke minggu ke-4 (p<0,05). Temuan ini mengindikasikan bahwa intervensi tersebut memberikan dampak positif yang signifikan dan berkelanjutan terhadap penurunan kelelahan pasien. Kata Kunci:  Intradialytic Flexybility Exercise, Fatigue, Gagal Ginjal Kronis